2002
DOI: 10.1038/sj.ijo.0801855
|View full text |Cite
|
Sign up to set email alerts
|

Habitual meal frequency and energy intake regulation in partially temporally isolated men

Abstract: OBJECTIVE: Assessment of a possible relationship between habitual as well as manipulated meal frequency, blood glucose pattern, macronutrient-and energy intake (EI), and energy intake regulation in partially temporally isolated men. DESIGN: A partially temporally isolated within-subject design assessing energy intake regulation in spite of intervention. Intervention consisted of manipulating meal frequency by offering iso-energetic (1 MJ) preloads high in fat or carbohydrate (CHO), with the same energy density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…This result could be in agreement with a previous study, 18 but in contrast to others. [19][20][21][22] A recent study 23 also reported no association between meal frequency and energy intake. The present study also shows no significant differences between the two meal patterns in the appetite ratings after the test meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could be in agreement with a previous study, 18 but in contrast to others. [19][20][21][22] A recent study 23 also reported no association between meal frequency and energy intake. The present study also shows no significant differences between the two meal patterns in the appetite ratings after the test meal.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,[18][19][20][21][22][23] Studies considering appetite ratings derived from visual analogue scales (VAS) have been undertaken in lean 24 and obese. 25 In both cases, subjects were given a large breakfast on one occasion or 5 smaller meals at hourly intervals on the other.…”
Section: Introductionmentioning
confidence: 99%
“…may be more closely related to compositional aspects that promote slower rates of digestion and absorption in the gut, rather than postprandial glycaemia per se . Habitual meal frequency is based upon a cluster of related factors including macronutrient composition of the food, sweetness perception, hunger suppression, but also on blood glucose declines and average blood glucose levels (166). Changes in glycaemia thus appear as only one of the criteria involved in food intake regulation.…”
Section: Future Developmentsmentioning
confidence: 99%
“…The guidelines were presented as information letters applicable and readable for every individual, and contained general information based on scientific research about diet (eg portion size, meal frequency, macronutrients, snacks, breakfast, fibers and water, etc [27][28][29][30] ), or about exercise (eg physical activity level, low/ moderate/high intensity, activity induced decrease in appetite, activity energy expenditure as compared to total energy expenditure, maintain fat-free mass (FFM), prevent osteoporosis, importance of walking and cycling, etc [31][32][33][34][35][36][37] ), or about diet þ exercise, 38,39 or about all other cues but diet þ exercise (placebo or distraction from obsessive dieting). Frequent dieting is one of the strategies for subjects to maintain their weight, while it has been shown that this can have a contrary effect.…”
Section: Experimental Designmentioning
confidence: 99%